Analisis Peran Rumah Detensi Imigrasi (Rudenim) Terhadap Imigran: Studi Kasus Kota Tanjungpinang - Nivaldi Romadona; Fika Ramdhani; Ismet Akbar; Lukman Nur Hakim; Iswandio Fanreza; Kustiawan Kustiawan (CV. ITTC INDONESIA, 2025)
This study aims to examine and analyze the role of the Immigration Detention Center (Rudenim) in the management and handling of immigrants in Tanjungpinang City, as well as to identify the inhibiting factors faced by Rudenim in carrying out its duties. The research employs a descriptive qualitative method with a case study approach, using data collection techniques such as interviews, observations, and documentation. The findings indicate that Rudenim Tanjungpinang plays a strategic role in the processes of detention, transfer, repatriation, and deportation of immigrants, in accordance with the Decree of the Minister of Law and Human Rights Number M.01-PR.07.04. In addition to its administrative functions, Rudenim also strives to carry out its duties with a humanistic approach, especially in dealing with stateless individuals. The main challenges include the complex process of nationality identification. This study recommends enhancing inter-agency coordination and strengthening international cooperation to support Rudenim’s functions more effectively.